Effects of nanoparticles on evaporative self-assembly in nanofluid droplets - Siti Nur Atikah Mohd Dermawan (2014)
The following thesis details the research done and experiments conducted as part of the Drying Pattern Evaporation Study. Previously published papers on the subject matter have been reviewed and taken into consideration when carrying out the experiments. In all the experiments conducted, Al2O3, Graphite, and TiO2 were used with the surfactant, CTAB. It is noted that rings form at the perimeters of the nanofluid droplets during evaporation, and were left even after the process was over. Investigations went underway right after, based on the factors that might have been the determinants to the drying pattern – species, surfactant concentration, particle concentration and particle size. In the Species Study, each specie’s droplets was unique to the next, while in mixtures, their droplet patterns displayed a combination of characteristics of its parents’. The Surfactant Study proved that with increase in CTAB concentrations, the nanofluid droplets’ ring widths increases, with a more significant increase in ring width for the droplet pattern in mixtures. The third study on Particle Concentration displayed a phase separation phenomena in which lesser phase separation is observed with increase in particle concentration. In the final study on Particle Size, different sizes of Al2O3 – 5nm, 40nm and 150nm – were tested. Findings showed that particle size directly affected the aggregation of particles within the nanofluid droplet, with more particle aggregation observed in droplets of larger particle sizes, or in mixture droplets. In conclusion, all the factors initially hypothesised to have had an effect on droplet pattern turned up with positive results, albeit no two factors are independent of each other.